The enormous radio - Cheever, John. (Mankato, Minn. : Creative Education, 1983)
A married couple's new radio tunes into the private lives of everybody else in their New York City apartment building.
Keywords: Eavesdropping -- Fiction; Marriage -- Fiction; Radio -- Fiction; Apartment houses -- Fiction; New York (N.Y.) -- Fiction